FORECASTING ANORGANIC WASTE VOLUME AFTER THE IMPLEMENTATION OF PLASTIC BAG RESTRICTIONS USING DOUBLE EXPONENTIAL SMOOTHING METHOD AT BOGOR CITY - Ani Andriyati; Embay Rohaeti (Universitas Pakuan, 2020)
Garbage is a classic problem causing environmental and ecosystem damage in every region, including in Bogor City. Plastic is one of the largest types of inorganic waste that causes ecosystem damage. In one day 1,7 tons of plastic waste are produced from a modern shopping center in Bogor. Several attempts were made to reduce the volume of inorganic waste. Since July 2018 the Regional Government of Bogor City has issued a regulation restricting the use of plastic bags in the modern market as an effort to reduce inorganic waste, especially plastic waste. Forecasting the volume of inorganic waste after the enactment of this regulation is needed as an evaluation step. The double exponential smoothing hole model is suitable for linear data trends. This is in accordance with the condition of inorganic waste volume data which tends to have a linear trend. Forecasting produces parameter parameter values Î± (level) 0,78 and Î³ (trend) 0,09 also MAPE 7,25%. The forecast results show that the volume of inorganic waste tends to increase in 2020. In order for this regulation to be optimal, it is necessary to consider applying these regulations not only in the modern market but also in the traditional market. In addition, it is also necessary to find an alternative to substitute for plastic so as not to switch to other inorganic types.